Mr Gum and the goblins - Stanton, Andy 1973- (Egmont, 2007)
Good evening, brave reader! But you are brave enough to join Polly and Friday as they climb Goblin mountain to battle the forces of evil? For be warned. This book is full of swords and trolls and witches and a thing that looks like a gherkin. And somehow that old roo-de-lally Mr Gum is all mixed up in it too.Shabba me whiskers , it's a Burpin Epic!
Keywords: Gum, Mr. (Fictitious character) / Juvenile fiction; Einsiedler; Bosheit; Protest; Mädchen; Kinderbuch